The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1590/s1516-14392006000300015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of rare earth oxides doping SnO2.(Co1/4,Mn3/4)O-based varistor system

Abstract: The present paper aims to verify the inuence of rare earth oxide such as lanthanum (La2O3) and neodymium (Nd2O3) doping SnO2 + 0.25%CoO + 0.75%MnO2 + 0.05%Ta2O5 system. The analysis focus on microstructural inuence on electrical properties. Microstructural analysis were made by using Transmission Electron Microscopy (TEM) at different regions of the samples. From such analysis it was found that La2O3 and Nd2O3 oxides cause heterogeneous segregation and precipitation at grain boundary concerning cobalt and mang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Tin(IV) oxide can be doped with oxides of iron or manganese for excellent uses. 5,6 Zinc oxide nanoparticles have vast applications, such as in the ceramics industry, 7 medicine, 8 food additives, 9 and UV absorbers 10 and in nuclear reactors as a corrosion preventer. 11 A fascinating property of mixed metal oxides is their versatility; they can be used for many purposes with high efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Tin(IV) oxide can be doped with oxides of iron or manganese for excellent uses. 5,6 Zinc oxide nanoparticles have vast applications, such as in the ceramics industry, 7 medicine, 8 food additives, 9 and UV absorbers 10 and in nuclear reactors as a corrosion preventer. 11 A fascinating property of mixed metal oxides is their versatility; they can be used for many purposes with high efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that the vacancies are preferentially created at the surface of the SnO 2 grains, increasing oxygen diffusion at grain boundaries and then promoting densification. 7 Although multi-components system such as SnO 2 -CoONb 2 O 5 -Cr 2 O 3 lead apparently to single-phase ceramics, 1 in the binary system CoO-SnO 2 the solid solution limit seems very weak since polyphased ceramics are obtained. 6 The ionic radius mismatch between Co and Sn is very small (r Co 2+ = 0.074 nm, r Sn 4+ = 0.071 nm, r = 0.003 nm).…”
Section: Introductionmentioning
confidence: 99%
“…16 Doping with various compounds has been investigated (e.g., with CuO). 17 Doping with cobalt and manganese gives a material that can be used in high voltage, for example; in addition, tin(IV) oxide can be doped with the oxides of iron or manganese. 18 J. K. Srivastava et al 19 reported on the microstructural proprieties of the PbO-doped SnO 2 sensor for the detection of methanol, propanol, and acetone.…”
Section: Introductionmentioning
confidence: 99%